Identifikasi Potentially Inappropriate Medication (PIM) Berdasarkan Beers Criteria 2023 pada Pasien Geriatri - Laduna Aniq (Jurnal Kesmas Asclepius, 2025)
This study aims to identify the characteristics of geriatric patients, the types of medication administered, and evaluate the incidence of Potentially Inappropriate Medication (PIM) based on the 2023 Beers Criteria at Suryakencana Pharmacy in Sukabumi City. The study used a retrospective descriptive observational design with a quantitative approach. Data were obtained from prescriptions and medical records of geriatric patients who filled the medication between December 2024 and June 2025. Analysis was performed by matching the prescribed medication with the criteria in the 2023 Beers Criteria. A total of 100 patients were included in the study sample, with the majority aged 60–74 years (73.74%) and female (62%). Most patients received ≤5 types of medication (95%). The most common diagnoses came from the nervous system disease group, with the dominant comorbidities being hypertension and diabetes mellitus. The most common medications included in the Beers Criteria category were non-selective NSAIDs such as diclofenac (55.55%) and the anticonvulsant gabapentin (15.66%). PIM incidents were found primarily in the categories of "drugs to avoid" (47.09%) and "use with caution" (2.90%). The study's conclusion confirms that the high incidence of PIM in geriatric patients indicates the need for consistent application of the Beers Criteria in pharmaceutical care practices to improve therapeutic safety in the elderly. Keywords: Beers Criteria, Geriatri, Potentially Inappropriate Medication (PIM).